Preprocedural Anxiety in the Transradial Cardiac Catheterization Era. Issue 4 (July 2021) - Fernandez, Ritin; Ellwood, Laura; Lord, Heidi; Curtis, Elizabeth; Khoo, John; Lee, Astin; Weaver, James
Abstract : Background: Transradial cardiac catheterization is increasingly being used for the management of coronary artery disease given the low risk of procedural discomfort and complications with this approach. However, the evidence relating to preprocedural anxiety levels in these patients is scarce. Objective: The aim of this study was to evaluate the anxiety levels and the predictors of anxiety in patients undergoing transradial cardiac catheterization procedures. Methods: Data were collected using a self-administered survey. Anxiety was measured using the Spielberg's State-Trait Anxiety Inventory questionnaire. Multiple regression analysis was used to identify whether gender, age, family history of heart disease, smoking status, history of depression, and trait anxiety scores were predictors of preprocedural anxiety. Results: A total of 198 patients participated in this study. More than half of the patients (53.5%) were classified as having a high state anxiety level. The mean (SD) preprocedural trait and state anxiety scores were 35.34 (9.8) and 36.43 (11.4), respectively. Female patients, those younger than 65 years, current smokers, and those with a family history of heart disease, a history of depression, and a history of anxiety had significantly higher anxiety scores. Having high trait anxiety scores was the only predictor of preprocedural anxiety. Conclusion: Although the transradial approach has a low procedural risk and causes less discomfort to the patient, anxiety persists in more than 50% of patients, with trait anxiety being the best predictor. Nurses should therefore try to decrease anxiety levels in the preprocedural phase to minimize postprocedural adverse outcomes in this group of patients.